American Society for Transplantation and Cellular Therapy Series: #6 - Management of Invasive Candidiasis in Hematopoietic Cell Transplant Recipients - Neofytos, Dionysios; Steinbach, William J.; Hanson, Kimberly; Carpenter, Paul A.; Papanicolaou, Genovefa A.; Slavin, Monica A. (Transplantation and Cellular Therapy, 2023)
The Practice Guidelines Committee of the American Society of Transplantation and Cellular Therapy (ASTCT) partnered with its Transplant Infectious Disease Special Interest Group (TID-SIG) to update its 2009 compendium-style infectious disease guidelines for hematopoietic cell transplantation (HCT). A completely new approach was taken with the goal of better serving clinical providers by publishing each standalone topic in the infectious disease series as a concise format of frequently asked questions (FAQ), tables and figures.[1] Adult and pediatric infectious disease and HCT content experts developed, then answered FAQs, and finalized topics with harmonized recommendations that were made by assigning an A through E strength of recommendation paired with a level of supporting evidence graded I through III. This sixth guideline in the series focuses on invasive candidiasis (IC) with FAQs to address epidemiology, clinical diagnosis, prophylaxis and treatment of IC, plus special considerations for pediatric, cord blood, haploidentical and T-cell depleted HCT recipients, CAR-T cell recipients, as well as future research directions.
Keywords: Diagnosis; Epidemiology; Guidelines; Hematopoïetic Cell Transplant; Invasive Candidiasis; Prophylaxis; treatment

American Society for Transplantation and Cellular Therapy Series: #4 - Cytomegalovirus treatment and management of resistant or refractory infections after hematopoietic cell transplantation - Yong, Michelle K.; Shigle, Terri Lynn; Kim, Yae-Jean; Carpenter, Paul A.; Chemaly, Roy F.; Papanicolaou, Genovefa A. (Transplantation and Cellular Therapy, 2021)
The Practice Guidelines Committee of the American Society of Transplantation and Cellular Therapy (ASTCT) partnered with its Transpl. Infect. Dis. Special Interest Group (TID-SIG) to update its 2009 compendium-style infectious disease guidelines for hematopoietic cell transplantation (HCT). A new approach was employed with the goal of better serving clinical providers by publishing each standalone topic in the infectious diseases series as a concise format of frequently asked questions (FAQ), tables, and ﬁgures. Adult and pediatric infectious diseases and HCT content experts developed and answered FAQs. Topics were ﬁnalized with harmonized recommendations that were made by assigning an A through E strength of recommendation paired with a level of supporting evidence graded I through III. The fourth topic in the series focuses on the management and treatment of cytomegalovirus (CMV) resistant and refractory infections. The diagnosis, deﬁnitions of resistant and refractory CMV, risk factors, virological genotypes and treatment algorithms are reviewed.

American Society for Transplantation and Cellular Therapy Series: #3—Prevention of Cytomegalovirus Infection and Disease After Hematopoietic Cell Transplantation - Hakki, Morgan; Aitken, Samuel L.; Danziger-Isakov, Lara; Michaels, Marian G.; Carpenter, Paul A.; Chemaly, Roy F.; Papanicolaou, Genovefa A.; Boeckh, Michael; Marty, Francisco M. (Transplantation and Cellular Therapy, 2021)
The Practice Guidelines Committee of the American Society for Transplantation and Cellular Therapy partnered with its Transplant Infectious Disease Special Interest Group to update its 2009 compendium-style infectious diseases guidelines for the care of hematopoietic cell transplant (HCT) recipients. A new approach was taken with the goal of better serving clinical providers by publishing each standalone topic in the infectious disease series as a concise format of frequently asked questions (FAQ), tables, and ﬁgures. Adult and pediatric infectious disease and HCT content experts developed and answered FAQs. Topics were ﬁnalized with harmonized recommendations that were made by assigning an A through E strength of recommendation paired with a level of supporting evidence graded I through III. The third topic in the series focuses on the prevention of cytomegalovirus infection and disease in HCT recipients by reviewing prophylaxis and preemptive therapy approaches; key deﬁnitions, relevant risk factors, and diagnostic monitoring considerations are also reviewed.

American Society for Transplantation and Cellular Therapy Series #10: Management of Parainfluenza and Human Metapneumovirus Infections in Hematopoietic Cell Transplantation and Cellular Therapy Recipients - Batista, Marjorie Vieira; Chaer, Firas El; Englund, Janet A.; Boeckh, Michael; Carpenter, Paul A.; Dadwal, Sanjeet S.; Waghmare, Alpana; Navarro, David; Hirsch, Hans H.; Piñana, Jose Luis; Papanicolaou, Genovefa A.; Chemaly, Roy F. (Transplantation and Cellular Therapy, Official Publication of the American Society for Transplantation and Cellular Therapy, 2025)
Publisher: Elsevier
Keywords: Cellular therapy; Guidelines; Hematopoietic cell transplantation; Human metapneumovirus; Parainfluenza virus; Paramyxovirus

American Society of Transplantation and Cellular Therapy Series: #8-Management and Prevention of Non-Aspergillus Molds in Hematopoietic Cell Transplantation Recipients - Douglas, Abby P.; Lamoth, Frederic; John, Teny M.; Groll, Andreas H.; Shigle, Terri Lynn; Papanicolaou, Genovefa A.; Chemaly, Roy F.; Carpenter, Paul A.; Dadwal, Sanjeet S.; Walsh, Thomas J.; Kontoyiannis, Dimitrios P. (Transplantation and Cellular Therapy, Official Publication of the American Society for Transplantation and Cellular Therapy, 2025)
Publisher: Elsevier
Keywords: Guideline; Hematopoietic cell transplant; Invasive fungal infection; Mold

American Society for Transplantation and Cellular Therapy Series #11: Updated Cytomegalovirus Guidelines in Hematopoietic Cell Transplant and Cellular Therapy Recipients - Khawaja, Fareed; Zamora, Danniel; Yong, Michelle K.; Hakki, Morgan; Goscicki, Breana K.; Danziger-Isakov, Lara; Lin, Andrew; Carpenter, Paul A.; Boeckh, Michael; Papanicolaou, Genovefa A.; Dadwal, Sanjeet S.; Chemaly, Roy F. (Transplantation and Cellular Therapy, Official Publication of the American Society for Transplantation and Cellular Therapy, 2025)
Publisher: Elsevier
Keywords: Cellular therapy; Chimeric antigen receptor therapy; Cytomegalovirus; Hematopoietic cell transplant

American Society of Transplantation and Cellular Therapy Series: #7 - Management of Respiratory Syncytial Virus Infections in Hematopoietic Cell Transplant Recipients - Chaer, Firas El; Kaul, Daniel R.; Englund, Janet A.; Boeckh, Michael; Batista, Marjorie V.; Seo, Susan K.; Carpenter, Paul A.; Navarro, David; Hirsch, Hans H.; Ison, Michael G.; Papanicolaou, Genovefa A.; Chemaly, Roy F. (Transplantation and Cellular Therapy, 2023)
The Practice Guidelines Committee of the American Society of Transplantation and Cellular Therapy (ASTCT) partnered with its Transplant Infectious Disease Special Interest Group (TID-SIG) to update the 2009 compendium-style infectious disease guidelines for hematopoietic cell transplantation (HCT). A new approach was adopted to better serve clinical providers by publishing each standalone topic in the infectious disease series in a concise format of frequently asked questions (FAQ), tables, and figures. Experts in HCT and infectious diseases identified FAQs and then provided answers based on the strength of the recommendation and the level of supporting evidence. In the seventh guideline in the series, we focus on the respiratory syncytial virus (RSV) with FAQs addressing epidemiology, clinical diagnosis, prophylaxis, and treatment. Special consideration was given to RSV in pediatric, cord blood, haploidentical, and T cell-depleted HCT and chimeric antigen receptor T cell therapy recipients, as well as to identify future research directions.

American Society for Transplantation and Cellular Therapy Series #9: Management of Human Herpesvirus 6B After Hematopoietic Cell Transplantation and Chimeric Antigen Receptor-T-Cell Therapy - Kampouri, Eleftheria; Handley, Guy; Phan, Tuan L.; Lee, Yeon Joo; Shaw, Ryan; Carpenter, Paul A.; Dadwal, Sanjeet S.; Chemaly, Roy F.; Papanicolaou, Genovefa A.; Ogata, Masao; Boeckh, Michael; Zerr, Danielle M.; et al. (Transplantation and Cellular Therapy, 2025)
The Practice Guidelines Committee and the Transplant Infectious Disease Special Interest Group of the American Society for Transplantation and Cellular Therapy developed guidelines focusing on human herpesvirus 6B (HHV-6B). A compendium-style approach was used to address a series of standalone frequently asked questions (FAQs), supported by tables and figures to spotlight key concepts. Adult and pediatric infectious disease and hematopoietic cell transplantation (HCT) content experts developed these FAQs and finalized recommendations after consensus was reached. This ninth topic in the series focuses on the relevant risk factors, diagnostic considerations, prophylaxis, and treatment approaches relevant to HHV-6B infections after HCT and chimeric antigen receptor-T-cell therapy.
Keywords: Allogeneic hematopoietic cell transplant; CAR-T-cell therapy; Encephalitis; HHV-6; Inherited chromosomally integrated HHV-6

Revised Guidelines for Coronavirus Disease 19 Management in Hematopoietic Cell Transplantation and Cellular Therapy Recipients (August 2022) - Dioverti, Veronica; Boghdadly, Zeinab El; Shahid, Zainab; Waghmare, Alpana; Abidi, Maheen Z.; Pergam, Steven; Boeckh, Michael; Dadwal, Sanjeet; Kamboj, Mini; Seo, Susan; Chemaly, Roy F.; Papanicolaou, Genovefa A. (Transplantation and Cellular Therapy, Official Publication of the American Society for Transplantation and Cellular Therapy, 2022)
Publisher: Elsevier
Keywords: COVID-19; Cellular therapy; Hematopoietic cell transplantation; SARS-CoV-2; cellular therapy; hematopoietic cell transplantation

Drug Resistance Assessed in a Phase 3 Clinical Trial of Maribavir Therapy for Refractory or Resistant Cytomegalovirus Infection in Transplant Recipients - Chou, Sunwen; Alain, Sophie; Cervera, Carlos; Chemaly, Roy F.; Kotton, Camille N.; Lundgren, Jens; Papanicolaou, Genovefa A.; Pereira, Marcus R.; Wu, Jingyang J.; Murray, Rose Ann; Buss, Neil E.; Fournier, Martha (The Journal of Infectious Diseases, 2023)
BACKGROUND: This drug resistance analysis of a randomized trial includes 234 patients receiving maribavir and 116 receiving investigator-assigned standard therapy (IAT), where 56% and 24% respectively cleared cytomegalovirus DNA at week 8 (treatment responders). METHODS: Baseline and post-treatment plasma samples were tested for mutations conferring drug resistance in viral genes UL97, UL54 and UL27. RESULTS: At baseline, genotypic testing revealed resistance to ganciclovir, foscarnet or cidofovir in 56% of patients receiving maribavir and 68% receiving IAT, including 9 newly phenotyped mutations. Among them, 63% (maribavir) and 21% (IAT) were treatment responders. Detected baseline maribavir resistance mutations were UL27 L193F (n=1) and UL97 F342Y (n=3). Post-treatment, emergent maribavir resistance mutations were detected in 60 (26%) of those randomized to maribavir, including 49 (48%) of 103 non-responders and 25 (86%) of the 29 non-responders where viral DNA initially cleared then rebounded while on maribavir. The most common maribavir resistance mutations were UL97 T409M (n=34), H411Y (n=26) and C480F (n=21), first detected 26 to 130 (median 56) days after starting maribavir. CONCLUSIONS: Baseline maribavir resistance was rare. Drug resistance to standard cytomegalovirus antivirals did not preclude treatment response to maribavir. Rebound in plasma cytomegalovirus DNA while on maribavir strongly suggests emerging drug resistance. CLINICAL TRIALS REGISTRATION: NCT02931539 (SOLSTICE).
Keywords: Antiviral drug resistance; antiviral therapy; cytomegalovirus; maribavir

Comparative Emergence of Maribavir and Ganciclovir Resistance in a Randomized Phase 3 Clinical Trial for Treatment of Cytomegalovirus Infection - Chou, Sunwen; Winston, Drew J; Avery, Robin K; Cordonnier, Catherine; Duarte, Rafael F; Haider, Shariq; Maertens, Johan; Peggs, Karl S; Solano, Carlos; Young, Jo-Anne H; Gu, Joan; Pocock, Ginger; et al. (The Journal of Infectious Diseases, 2024)
Abstract Background Among 547 patients receiving maribavir or valganciclovir for first-episode cytomegalovirus infection after hematopoietic cell transplant, the treatment response rate was 69.6% and 77.4% respectively. Development of maribavir and ganciclovir resistance was compared after receiving either drug. Methods Viral mutations conferring drug resistance were analyzed in plasma DNA extracts at baseline and post-treatment. Results Prior antiviral drug exposure was limited, with only 2 instances of baseline drug resistance detected. An equal number (n=241) received valganciclovir or maribavir for at least 21 days (median 55-56 days). Among them, drug resistance mutations were detected in 24 (10%) maribavir recipients at 35-125 days (median 56) after starting therapy, including in 12 of 14 who experienced a viral load rebound while on therapy. Ganciclovir resistance mutations developed in 6 (2.5%) valganciclovir recipients at 66-110 days (median 90). One maribavir recipient developed a novel UL97 gene mutation (P-loop substitution G343A) that conferred strong maribavir and ganciclovir resistance in vitro. Viral clearance was confirmed in 17 (74%) of 23 patients with emergent maribavir resistance after re-treatment with an alternative CMV antiviral drug. Conclusion After 3-8 weeks of therapy, maribavir resistance emerged earlier and more frequently than ganciclovir resistance but was usually treatable using alternative therapy. Clinical Trials Registration NCT02927067 (AURORA)

Implementation of Molecular Surveillance After a Cluster of Fatal Toxoplasmosis at 2 Neighboring Transplant Centers - Isa, Flonza; Saito, Kohta; Huang, Yao-Ting; Schuetz, Audrey; Babady, N. Esther; Salvatore, Steven; Pessin, Melissa; van Besien, Koen; Perales, Miguel-Angel; Giralt, Sergio; Sepkowitz, Kent; Papanicolaou, Genovefa A.; et al. (Clinical Infectious Diseases: An Official Publication of the Infectious Diseases Society of America, 2016)
After a cluster of fatal toxoplasmosis among stem cell transplant recipients at 2 hospitals, surveillance with polymerase chain reaction (PCR) (blood) was instituted. Rate of reactivation among seropositive recipients was 2.2 and 16%. Parasitemia was successfully managed with preemptive treatment. For seropositive recipients unable to take prophylaxis, toxoplasma PCR surveillance should be routinely performed.

Maribavir for Refractory Cytomegalovirus Infections With or Without Resistance Post-Transplant: Results From a Phase 3 Randomized Clinical Trial - Avery, Robin K; Alain, Sophie; Alexander, Barbara D; Blumberg, Emily A; Chemaly, Roy F; Cordonnier, Catherine; Duarte, Rafael F; Florescu, Diana F; Kamar, Nassim; Kumar, Deepali; Maertens, Johan; Marty, Francisco M; et al. (Clinical Infectious Diseases, 2022)
Background. Therapies for refractory cytomegalovirus infections (with or without resistance [R/R]) in transplant recipients are limited by toxicities. Maribavir has multimodal anti-cytomegalovirus activity through the inhibition of UL97 protein kinase. Methods. In this phase 3, open-label study, hematopoietic-cell and solid-organ transplant recipients with R/R cytomegalovirus were randomized 2:1 to maribavir 400 mg twice daily or investigator-assigned therapy (IAT; valganciclovir/ganciclovir, foscarnet, or cidofovir) for 8 weeks, with 12 weeks of follow-up. The primary endpoint was confirmed cytomegalovirus clearance at end of week 8. The key secondary endpoint was achievement of cytomegalovirus clearance and symptom control at end of week 8, maintained through week 16. Results. 352 patients were randomized (235 maribavir; 117 IAT). Significantly more patients in the maribavir versus IAT group achieved the primary endpoint (55.7% vs 23.9%; adjusted difference [95% confidence interval (CI)]: 32.8% [22.80–42.74]; P < .001) and key secondary endpoint (18.7% vs 10.3%; adjusted difference [95% CI]: 9.5% [2.02–16.88]; P = .01). Rates of treatment-emergent adverse events (TEAEs) were similar between groups (maribavir, 97.4%; IAT, 91.4%). Maribavir was associated with less acute kidney injury versus foscarnet (8.5% vs 21.3%) and neutropenia versus valganciclovir/ganciclovir (9.4% vs 33.9%). Fewer patients discontinued treatment due to TEAEs with maribavir (13.2%) than IAT (31.9%). One patient per group had fatal treatment-related TEAEs. Conclusions. Maribavir was superior to IAT for cytomegalovirus viremia clearance and viremia clearance plus symptom control maintained post-therapy in transplant recipients with R/R cytomegalovirus. Maribavir had fewer treatment discontinuations due to TEAEs than IAT.

Treatment for First Cytomegalovirus Infection Post-Hematopoietic Cell Transplant in the AURORA Trial: A Multicenter, Double-Blind, Randomized, Phase 3 Trial Comparing Maribavir with Valganciclovir - Papanicolaou, Genovefa A; Avery, Robin K; Cordonnier, Catherine; Duarte, Rafael F; Haider, Shariq; Maertens, Johan; Peggs, Karl S; Solano, Carlos; Young, Jo-Anne H; Fournier, Martha; Murray, Rose Ann; Wu, Jingyang; et al. (Clinical Infectious Diseases, 2023)
Background. Neutropenia may limit use of valganciclovir treatment for cytomegalovirus (CMV) infection following hematopoietic cell transplant (HCT). A phase 2 study indicated efficacy of maribavir with fewer treatment-limiting toxicities than valganciclovir. Methods. In this multicenter, double-blind, phase 3 study, patients with first asymptomatic CMV infection post-HCT were stratified and randomized 1:1 to maribavir 400 mg twice daily or valganciclovir (dose-adjusted for renal clearance) for 8 weeks with 12 weeks follow-up. Primary T endpoint was confirmed CMV viremia clearance at week 8 (primary hypothesis of noninferiority margin of 7.0%). Key secondary endpoint was a composite of the primary endpoint IP with no findings of CMV tissue-invasive disease at week 8, through week 16. Treatmentemergent adverse events (TEAEs) were assessed. R Results. Among patients treated (273 maribavir; 274 valganciclovir), the primary endpoint of C non-inferiority of maribavir was not met (maribavir, 69.6%; valganciclovir, 77.4%; adjusted S difference [95% confidence interval (CI)]: −7.7% [−14.98, −0.36]; lower limit of 95% CI of treatment difference exceeded −7.0%). At week 16, 52.7% and 48.5% of patients treated U (maribavir and valganciclovir, respectively) maintained CMV viremia clearance without tissueinvasive disease (adjusted difference [95% CI]: 4.4% [−3.91, 12.76]). With maribavir (versus N valganciclovir), fewer patients experienced neutropenia (16.1% and 52.9%) or discontinued due A to TEAEs (27.8% and 41.2%). Discontinuations were mostly due to neutropenia (maribavir, M 4.0%; valganciclovir, 17.5%). Conclusions. Although non-inferiority of maribavir to valganciclovir for the primary endpoint was not achieved based on the prespecified non-inferiority margin, maribavir demonstrated comparable CMV viremia clearance during post-treatment follow-up, with fewer D discontinuations due to neutropenia.